Asbestos in toys: an exemplary case - Silvestri, Stefano; Di Benedetto, Francesco; Raffaell, Corrado; Veraldi, Angela (Scandinavian Journal of Work, Environment & Health, 2016)
' ' OBJECTIVES ': 'DAS was an artificial clay which, once molded, hardened at room temperature. It was largely used as a toy between 1963 and 1975 in Italy, Netherlands, Germany, UK and Norway. This case report describes and reports the presence of asbestos in DAS. ' ' METHODS ': 'We investigated the presence of asbestos in DAS using light and electron microscopy on samples of the original material. We searched administrative documents at the State Archive of Turin and conducted interviews with past employees on annual production, suppliers, and purchasers. ' ' RESULTS ': 'The analytical tests confirmed the presence of asbestos fibers in DAS: about 30% of its composition. The documents found at the State Archive confirmed the annual purchase of hundreds tons of raw asbestos from the Amiantifera di Balangero, the Italian asbestos mine. DAS was found to be used also within craftsmanship. ' ' CONCLUSIONS ': 'Asbestos fibers in DAS may have caused exposure to production workers and a variety of users, including artists, teachers, and children. Over 13 years, about 55 million packs of DAS were produced and sold. The number of users is difficult to estimate but may have been in the order of millions. In Italy, a specific question on the use of DAS has been included in a routinely used mesothelioma questionnaire. As DAS was exported to other countries, our findings suggest that mesothelioma patients should be asked about their past use of DAS, in particular individuals not reporting a clear past asbestos exposure. Additionally, this discovery shows the incompleteness of records on asbestos uses and suggests to test items, including toys, imported from countries where asbestos is not forbidden.
Keywords: artist; asbestos; asbestos-containing product; case report; childhood exposure; chrysotile; epidemiology; mesothelioma; surveillance; teacher; teaching item; toy